2008
DOI: 10.2217/14796694.4.4.553
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Diffuse Gastric Cancer: Surgery, Surveillance and Unanswered Questions

Abstract: Hereditary diffuse gastric cancer (HDGC) is an inherited cancer-susceptibility syndrome characterized by autosomal dominance and high penetrance. In 30-50% of cases, a causative germline mutation in CDH1, the E-cadherin gene, may be identified. Female carriers of CDH1 mutations also have an increased (20-40%) risk of lobular breast cancer. Endoscopic surveillance of patients with CDH1 mutations is ineffective because early foci of HDGC are typically small and underlie normal mucosa. CDH1 mutation carriers are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Additionally, the prevalence of mutations in patients without a family history of GC was unknown; thus, the IGCLC believed it was premature to offer genetic testing for sporadic cases [3]. Since then, the prevalence of CDH1 mutations in families with a history of lobular breast cancer and/or colon cancer, as well as the prevalence of CDH1 mutations among young individuals with GC and no family history of the disease from low-incidence populations, has been documented and the criteria for CDH1 testing have been modified [5,7,8,11,[15][16][17][18] (Table 1). We found that patients with a family history of GC (histology unknown) and documented DGC who tested positive for CDH1 mutations also had a family history of breast cancer and/or colon cancer ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, the prevalence of mutations in patients without a family history of GC was unknown; thus, the IGCLC believed it was premature to offer genetic testing for sporadic cases [3]. Since then, the prevalence of CDH1 mutations in families with a history of lobular breast cancer and/or colon cancer, as well as the prevalence of CDH1 mutations among young individuals with GC and no family history of the disease from low-incidence populations, has been documented and the criteria for CDH1 testing have been modified [5,7,8,11,[15][16][17][18] (Table 1). We found that patients with a family history of GC (histology unknown) and documented DGC who tested positive for CDH1 mutations also had a family history of breast cancer and/or colon cancer ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…We also found a higher percentage of women (59%) had documented DGC compared to men (41%) (Appendix B). Patients fulfilling the modified criteria have an estimated 30-50% likelihood of harboring CDH1 mutations [8,16]. Isolated cases of DGC in young individuals from a low-incidence population have a 20% probability of harboring a CDH1 mutation [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations